Nitrogen cycling in sediments on the NW African margin inferred from N and O isotopes in benthic chambers - Dale, Andrew W.; Clemens, David; Dähnke, Kirstin; Korth, Frederike; Wankel, Scott D.; Schroller-Lomnitz, Ulrike; Wallmann, Klaus; Sommer, Stefan (Frontiers in Marine Science, 2022)
Benthic nitrogen cycling in the Mauritanian upwelling region (NW Africa) was studied in June 2014 from the shelf to the upper slope where minimum bottom water O2 concentrations of 25 µM were recorded. Benthic incubation chambers were deployed at 9 stations to measure fluxes of O2, dissolved inorganic carbon (DIC) and nutrients (NO3-, NO2-, NH4+, PO43-, H4SiO4) along with the N and O isotopic composition of nitrate (δ15N-NO3- and δ18O-NO3-) and ammonium (δ15N-NH4+). O2 and DIC fluxes were similar to those measured during a previous campaign in 2011 whereas NH4+ and PO43- fluxes on the shelf were 2 – 3 times higher and possibly linked to a long-term decline in bottom water O2 concentrations. The mean isotopic fractionation of NO3- uptake on the margin, inferred from the loss of NO3- inside the chambers, was 1.5 ± 0.4 ‰ for 15/14N (15ϵapp) and 2.0 ± 0.5 ‰ for 18/16O (18ϵapp). The mean 18ϵapp:15ϵapp ratio on the shelf (< 100 m) was 2.1 ± 0.3, and higher than the value of 1 expected for microbial NO3-reduction. The 15ϵapp are similar to previously reported isotope effects for NO3- respiration in marine sediments but lower than determined in 2011 at a same site on the shelf. The sediments were also a source of 15N-enriched NH4+ (9.0 ± 0.7 ‰). A numerical model tuned to the benthic flux data and that specifically accounts for the efflux of 15N-enriched NH4+ from the seafloor, predicted a net benthic isotope effect of N loss (15ϵsed) of 3.6 ‰; far above the more widely considered value of 0‰. This result is further evidence that the assumption of a universally low or negligible benthic N isotope effect is not applicable to oxygen-deficient settings. The model further suggests that 18ϵapp:15ϵapp trajectories > 1 in the benthic chambers are most likely due to aerobic ammonium oxidation and nitrite oxidation in surface sediments rather than anammox, in agreement with published observations in the water column of oxygen deficient regions.